2013
DOI: 10.1007/s10616-012-9530-6
|View full text |Cite
|
Sign up to set email alerts
|

Considerations regarding use of solvents in in vitro cell based assays

Abstract: Cell culture systems are widely used for the investigation of in vitro immunomodulatory effects of medicines and natural products. Since many pharmacological relevant compounds are water-insoluble, solvents are frequently used in cell based assays. Although many reports describe the cellular effects of solvents at high concentrations, only a few relate the effects of solvents used at low concentrations. In this report we investigate the interference of three commonly used solvents: Dimethyl sulfoxide (DMSO), e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
103
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(109 citation statements)
references
References 17 publications
4
103
1
1
Order By: Relevance
“…al., showed that 1% DMSO is a critical concentration, because lower concentrations will result in increased cellular activation while higher concentrations will exert inhibitory effects. [31] This was the case of antibacterial assay in the present study, the negative control (DMSO) did not show any inhibitory activity. To the best of our knowledge, the aqueous crude extract of B. serrate antileishamanial activity has not been studied before.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…al., showed that 1% DMSO is a critical concentration, because lower concentrations will result in increased cellular activation while higher concentrations will exert inhibitory effects. [31] This was the case of antibacterial assay in the present study, the negative control (DMSO) did not show any inhibitory activity. To the best of our knowledge, the aqueous crude extract of B. serrate antileishamanial activity has not been studied before.…”
Section: Discussionsupporting
confidence: 44%
“…This variation in the inhibitory activities of cells (bacteria and promastigotes) may be due to low concentration of saponin extracted from the resin or due to the low concentration of DMSO used in the extraction or may be due to poor permeability of saponin inside the cells due to low solubility. [31] It is not preferred to increase the concentration of DMSO above (0.5%) which may affect the assays. In a study conducted by Timm et.…”
Section: Discussionmentioning
confidence: 99%
“…Dimethyl sulfoxide (DMSO) was used to dissolve the inhibitors. DMSO can both decrease or increased inflammatory responses such as ROS production and IL-6 secretion 165,166 . Therefore DMSO control was used to exclude any artefacts.…”
Section: Inhibition Of Receptors and Signaling Pathwaysmentioning
confidence: 99%
“…Organic solvents are often used as a vehicle to dissolve hydrophobic compounds in cell biology experiments (1)(2)(3)(4). Besides strong solubility characteristics, they should be compatible with the culture medium without toxic effects on cells, since experiments with cell based systems are performed in growth medium (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Besides strong solubility characteristics, they should be compatible with the culture medium without toxic effects on cells, since experiments with cell based systems are performed in growth medium (2,3). Some of the commonly used organic solvents such as acetone (Log P, -0.24), ethanol (Log P, -0.31), dimethyl sulfoxide (DMSO) (Log P, -1.35) and dimethyl formamide (DMF) (Log P, -1.01) were selected in the current study.…”
Section: Introductionmentioning
confidence: 99%